How European aid works - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
How European aid works: A comparison of management systems and effectiveness by Aidan Cox, John Healey and Antonique Koning 1997 246pp price UKL15.95 ISBN 0 85003 243 1